Age of ash - Abraham, Daniel (Book one of the Kithamar trilogy, 2022)
"Kithamar is a center of trade and wealth, an ancient city with a long, bloody history where countless thousands live and their stories unfold. This is Alys's. When her brother is murdered, a petty thief from the slums of Longhill sets out to discover who killed him and why. But the more she discovers about him, the more she learns about herself, and the truths she finds are more dangerous than knives. Swept up in an intrigue as deep as the roots of Kithamar, where the secrets of the lowest born can sometimes topple thrones, the story Alys chooses will have the power to change everything"--